2014
DOI: 10.3109/00365513.2014.980313
|View full text |Cite
|
Sign up to set email alerts
|

Total plasma clearance versus urinary plasma clearance of51Cr-EDTA in patients with cirrhosis with and without fluid retention

Abstract: In patients with fluid retention and ascites ClP and corrected one-pool clearance overestimates GFR substantially. Although ClU may underestimate GFR slightly, patients with ascites should collect urine quantitatively in order to obtain a reliable measurement of GFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The study comprised 81 patients with cirrhosis. Detailed clinical and biochemical description of the study population has been published recently (Henriksen et al ., ). In brief, the diagnosis of cirrhosis was confirmed either by biopsy or by established clinical and ultrasonographic criteria.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The study comprised 81 patients with cirrhosis. Detailed clinical and biochemical description of the study population has been published recently (Henriksen et al ., ). In brief, the diagnosis of cirrhosis was confirmed either by biopsy or by established clinical and ultrasonographic criteria.…”
Section: Methodsmentioning
confidence: 97%
“…This method assumes that the indicator is distributed into an accessible interstitial space and that all indicator molecules are eventually excreted (Lassen & Perl, ; Peters, ). In agreement with this assumption, several investigations have shown that in patients without fluid retention there is only a minor difference between the total plasma clearance, determined by blood sampling alone, and the urinary plasma clearance, determined by plasma and quantitative urinary sampling (Bröchner‐Mortensen & Rödbro, ; Rehling et al ., ; Moore et al ., ; Henriksen et al ., , ). However, this difference in clearance measurement increases in patients with fluid retention, especially in those with fluid accumulation in bodily cavities, like ascites (Henriksen et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Other exogenous substances that are filtered solely by the glomerulus, such as 51 Cr‐EDTA require only a single injection and plasma sample collection instead of urine. However, the sole collection of plasma samples is not accurate in cirrhotic patients and could ignore the possible extrarenal clearance of the marker into ascites and/or edema, particularly when the samples are collected too early after the bolus administration . Recently, a 51 Cr‐EDTA‐based equation requiring few plasma samples has been applied in patients with cirrhosis and ascites.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…Renal dysfunction is a serious and common complication in advanced cirrhosis, associated with a high morbidity and mortality . Gold standard measurement of the glomerular filtration rate (GFR) based on Cr 51 ‐EDTA clearance is accurate but impractical for the repeated assessments of renal function that are required in cirrhosis . Serum creatinine is widely used as a renal biomarker, but it is insufficient for identifying renal failure in patients with cirrhosis partly because of muscle wasting, fluid retention, and analytical influence of bilirubin on the creatinine measurement .…”
Section: Introductionmentioning
confidence: 99%
“…Gold standard measurement of the glomerular filtration rate (GFR) based on Cr 51 ‐EDTA clearance is accurate but impractical for the repeated assessments of renal function that are required in cirrhosis . Serum creatinine is widely used as a renal biomarker, but it is insufficient for identifying renal failure in patients with cirrhosis partly because of muscle wasting, fluid retention, and analytical influence of bilirubin on the creatinine measurement . Plasma neutrophil gelatinase‐associated lipocalin (NGAL) and cystatin C are two promising emerging renal biomarkers, which have been implemented in the assessment of renal dysfunction in cirrhosis .…”
Section: Introductionmentioning
confidence: 99%